2022
DOI: 10.1039/d1cy02344f
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized UiO-66(Ce) for photocatalytic organic transformation: the role of active sites modulated by ligand functionalization

Abstract: Ligand functionalization has been considered as an efficient strategy to modulate the property of metal-organic frameworks (MOFs). In this work, a series of functionalized UiO-66(Ce)-X (X=H, CH3, Br, NO2) have...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 70 publications
(74 reference statements)
2
16
0
Order By: Relevance
“…22 Both FC-66 and FMC-1 exhibit typical peaks at 1556 and 1434 cm À1 for the stretching vibrations V assy (-COO-) and V sym (-COO-) of carboxylate in H 2 BDC, respectively. 23 With increasing calcination time, the characteristic peaks of the carboxylate for FMC-2 and FMC-3 disappear, and is consistent with the XRD results. Since specific surface area (SSA) is one of the important factors to influence the mimetic enzyme performance, N 2 adsorption measurements at 77 K were used to characterize the pore size distribution and Brunauer-Emmett-Teller specific surface area (S BET ) values of FMC-n. As shown in Fig.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…22 Both FC-66 and FMC-1 exhibit typical peaks at 1556 and 1434 cm À1 for the stretching vibrations V assy (-COO-) and V sym (-COO-) of carboxylate in H 2 BDC, respectively. 23 With increasing calcination time, the characteristic peaks of the carboxylate for FMC-2 and FMC-3 disappear, and is consistent with the XRD results. Since specific surface area (SSA) is one of the important factors to influence the mimetic enzyme performance, N 2 adsorption measurements at 77 K were used to characterize the pore size distribution and Brunauer-Emmett-Teller specific surface area (S BET ) values of FMC-n. As shown in Fig.…”
Section: Resultssupporting
confidence: 85%
“…22 Both FC-66 and FMC-1 exhibit typical peaks at 1556 and 1434 cm −1 for the stretching vibrations V assy (–COO–) and V sym (–COO–) of carboxylate in H 2 BDC, respectively. 23 With increasing calcination time, the characteristic peaks of the carboxylate for FMC-2 and FMC-3 disappear, and is consistent with the XRD results.…”
Section: Resultssupporting
confidence: 85%
“…They found that UiO-66(Ce) modified by CH 3 possesses stronger Lewis acid sites, which can generate more free radicals to degrade pollutants. 35 Integration with semiconductors is another effective strategy to build functional MOFs for sterilization. On the one hand, the high surface area ratio of MOFs is conducive to producing more catalytic sites and forming better contact between the reactors and the active sites.…”
Section: In Vitro Researchmentioning
confidence: 99%
“…They found that UiO-66(Ce) modified by CH 3 possesses stronger Lewis acid sites, which can generate more free radicals to degrade pollutants. 35…”
Section: Photocatalytic Inactivation Bacteria Based On Mof Composite ...mentioning
confidence: 99%
See 1 more Smart Citation